Fructose induces glucose-dependent insulinotropic polypeptide, glucagon-like peptide-1 and insulin secretion: Role of adenosine triphosphate-sensitive K(+) channels - Seino, Yusuke (J Diabetes Investig, 2015)
Adenosine triphosphate-sensitive K(+) (K(ATP)) channels play an essential role in glucose-induced insulin secretion from pancreatic β-cells. It was recently reported that the K(ATP) channel is also found in the enteroendocrine K-cells and L-cells that secrete glucose-dependent insulinotropic polypeptide (GIP) and glucagon-like peptide-1 (GLP-1), respectively. In the present study, we investigated the involvement of the K(ATP) channel in fructose-induced GIP, GLP-1 and insulin secretion in mice. Fructose stimulated GIP secretion, but pretreatment with diazoxide, a K(ATP) channel activator, did not affect fructose-induced GIP secretion under streptozotocin-induced hyperglycemic conditions. Fructose significantly stimulated insulin secretion in Kir6.2(+/+) mice, but not in mice lacking K(ATP) channels (Kir6.2(−/−)), and fructose stimulated GLP-1 secretion in both Kir6.2(+/+) mice and Kir6.2(−/−) mice under the normoglycemic condition. In addition, diazoxide completely blocked fructose-induced insulin secretion in Kir6.2(+/+) mice and in MIN6-K8 β-cells. These results show that fructose-induced GIP and GLP-1 secretion is K(ATP) channel-independent and that fructose-induced insulin secretion is K(ATP) channel-dependent.